MV-RLU - Jaeho Kim; Ajit Mathew; Sanidhya Kashyap; Madhava Krishnan Ramanathan; Changwoo Min (Proceedings of the Twenty-Fourth International Conference on Architectural Support for Programming Languages and Operating Systems, 2019)
Intense bowel activity on 99mTc-MDP bone scintigraphy is often dismissed as urinary contamination or radiopharmaceutical instability, but persistent uptake should prompt an anatomic search. A 68-year-old woman with metastatic cervical squamous cell carcinoma after radical pelvic surgery underwent bone scintigraphy for suspected left-foot metastasis. Images showed sacral/pelvic metastases, benign-appearing calcaneal uptake, and organized colonic activity. Contrast-enhanced CT revealed a complex fistulous tract connecting the left distal ureter, vaginal stump, rectum, and sigmoid colon. Follow-up pelvic SPECT/CT localized persistent activity to the rectosigmoid lumen, confirming fistula-related intraintestinal urine. Recognition redirected interpretation from artifact to actionable urinary-enteric fistula with clinical implications.